The effects of trust on life satisfaction in the context of WeChat use. (September 2019) - Li, Bi; Wu, Yan; Hao, Zhifeng; Yan, Xueming; Chen, Boyu
Highlights: WeChat use exerts a third variable effect on the influence of trust on life satisfaction. Perceived usefulness (PU) of WeChat shows a positive effect on life satisfaction. PU of WeChat mediates between institutional trust and life satisfaction. PU of WeChat mediates between intensity of WeChat use and life satisfaction. Institutional trust shows a direct effect on life satisfaction. Abstract: Although WeChat is a popular mobile communication tool and social networking site (SNS) with over one billion monthly active users, the study regarding the third variable effects of the newly emerging SNS is relatively few. To investigate the joint effects of trust and WeChat use on life satisfaction, the current study explored the effects of trust on life satisfaction and examined the mediating role of intensity of WeChat use (IWU) and the perceived usefulness (PU) of WeChat on those effects. A sample of 463 undergraduate students participated in the study, and structural equation modeling was applied to examine the hypothesized model based on questionnaire data. Results showed the mediating role of the PU of WeChat on the positive effects of trust in institutions and IWU on life satisfaction. Trust in institutions exerted a direct and indirect positive effect on life satisfaction. IWU positively influenced life satisfaction only through the PU of WeChat. These findings contribute to knowledge on the effects of trust and the causes of life satisfaction.